T cell adhesion to TCR and Beta-1 integrin ligands is differentially controlled by the SKAP55 N-terminus. - Ophir, Michael. (2017)
Abstract: Productive immune responses require optimal T cell activation. T cell activation is dependent on TCR-initiated signaling events that occur within compartmentalized signaling complexes known as SLP-76 microclusters. SLP-76 microclusters are sites of active tyrosine phosphorylation and enzymatic activity at the immune synapse. Furthermore, SLP-76 microclusters recruit a variety of adaptor molecules that provide scaffolding functions to maintain the integrity of the complex and to protect against the actions of down-regulating kinases, phosphatases, caspases and ubiquitin ligases. I propose that in addition to acting as hubs of catalytic activity that are required for calcium flux and changes in the transcriptional profile of T cells, SLP-76 microclusters act as points of adhesion that bridge the TCR to the actin cytoskeleton and influence the topology of the immune synapse so as to maintain stable T cell-APC conjugates. I hypothesize that SLP-76 microclusters act as T cell-specific podosomes that reinforce areas of tight contact with the APC surface, thereby enabling the TCR to act as an adhesion receptor that stabilizes the immune synapse for prolonged T cell-APC conjugate formation and optimal TCR signal transduction. In addition, I hypothesize that SLP-76 microclusters integrate inside-out signals from the TCR to integrins to reinforce the adhesive capability of the immune synapse during antigen recognition. Here I show that one key regulator of inside-out signaling, SKAP55, recruits to TCR-induced SLP-76 microclusters and impacts microcluster dynamics, TCR- mediated contact stability and T cell retention to anti-CD3-coated substrates or Beta1 integrin ligands. These are the first data to demonstrate a role for SKAP55 in T cell spreading and adhesion downstream of solo TCR ligation. I demonstrate that dimerization of the SKAP55 SH3 domains is sufficient for these processes but is not sufficient for communication to Beta1 integrins. Inside-out signaling to integrins is dependent on scaffolding interactions between the SKAP55 N-terminal dimerization motif (DM) and the adaptors RIAM and talin. In addition, I demonstrate that the SKAP55 DM is required for optimal expression of paxillin, an important regulator of Beta1 integrin-mediated adhesion and migration. Analysis of SKAP55 function within the context of SLP-76 microclusters has revealed diverse roles for this molecule in TCR and integrin-dependent adhesion and promises to provide important insight with respect to how diverse arms of TCR signaling are coordinated in space and time to promote T cell activation and ensuing immune responses.; Thesis (Ph.D.)--Tufts University, 2014.; Submitted to the Dept. of Immunology.; Advisor: Stephen Bunnell.; Committee: Henry Wortis, Ralph Isberg, David Thorley-Lawson, Cheleste Thorpe, and Kenneth Swanson.; Keyword: Immunology.